Depression among secondary school students: a comparison between urban and rural populations - Musa, Ramli; S., Adlina; Ariaratnam, Suthahar; AB, Edariah; Fadzil, Mohd Ariff; AHH, Narimah; AS, Nuraliza; I., Fauzi; C., Karuthan (The Hong Kong College of Psychiatry, 2008)
Introduction: Childhood depression is a debilitating psychiatric illness and has frequently been under-diagnosed. It is crucial to identify the condition early, as undetected cases may lead to detrimental psychosocial consequences in adulthood. Objective: The prevalence of depression among school children in Selangor and to compare it between urban and rural schools. Also to identify factors associated with depression in secondary school children. Method: 2 urban and 3 rural secondary schools were selected by 2-staged stratified random sampling to represent the population of secondary school children in the state of Selangor, Malaysia. A total of 2,048 school children were enrolled and the level of depression was measured by a self-rated scale, the Children’s Depression Inventory. Results: This study found that the prevalence of possible depressive students in Selangor was 10.3%. There was no difference in the prevalence of depression between rural and urban population. Factors associated with depression were being female, Chinese, parents with low educational level, and high number of siblings, smoking and alcohol abuse. Depression contributed significantly to suicidal tendencies. Conclusions: A sizable proportion of the secondary school children in this population potentially suffer from depression. Psychological interventions are needed to ease this psychological burden and ensure their well being.